Functional Expression of the Arachis hypogaea L. Acyl-ACP Thioesterases AhFatA and AhFatB Enhances Fatty Acid Production in Synechocystis sp. PCC6803 - Gao Chen (Energies, 2017)
Palmitoleic acid (C16:1) and stearic acid (C18:0) are precursors of polyunsaturated fatty acids, which are the focus of intensive global research due to their nutritional value, medicinal applications, and potential use as biofuel. Acyl-acyl carrier protein (ACP) thioesterases are intraplastidial enzymes that determine the types and amounts of fatty acids produced in plants and release fatty acids into the cytosol to be incorporated into glycerolipids. Based on amino acid sequence identity and substrate specificity, these enzymes are classified into two families, FatA and FatB. In this study, we cloned FatA and FatB thioesterases from Arachis hypogaea L. seeds and functionally expressed these genes, both individually and in tandem, in a blue-green alga Synechocystis sp. PCC6803. The heterologous expression of these genes in Synechocystis altered the fatty acid composition of lipids, resulting in a 29.5–31.6% increase in palmitoleic acid production and a 22.5–35.5% increase in stearic acid production. Moreover, the transgenic Synechocystis cells also showed significant increases in levels of oleic acid (C18:1, OA), linoleic acid (C18:2, LA), and α-linolenic acid (C18:3n3, ALA). These results suggest that the fatty acid profile of algae can be significantly improved by the heterologous expression of exogenous genes. This study not only provides insight into fatty acid biosynthesis, but also lays the foundation for manipulating the fatty acid content of cyanobacteria.